Bottom-up fabrication of InAs-on-nothing MOSFET using selective area molecular beam epitaxy. (19th November 2018) - Pastorek, Matej; Olivier, Aurélien; Lechaux, Yoann; Wichmann, Nicolas; Karatsori, Théano; Fahed, Maria; Bucamp, Alexandre; Addad, Ahmed; Troadec, David; Ghibaudo, Gérard; Desplanque, Ludovic; Wallart, Xavier; et al.
Abstract: In this paper we report on the fabrication and electrical characterization of InAs-on-nothing metal-oxide-semiconductor field-effect transistor composed of a suspended InAs channel and raised InAs n+ contacts. This architecture is obtained using 3D selective and localized molecular beam epitaxy on a lattice mismatched InP substrate. The suspended InAs channel and InAs n+ contacts feature a reproducible and uniform shape with well-defined 3D sidewalls. Devices with 1 μ m gate length present a saturation drain current ( I Dsat ) of 300 mA mm −1 at V DS = 0.8 V and a trans-conductance ( GM ) of 120 mS mm −1 at V DS = 0.5 V. In terms of electrostatic control, the devices display a minimal subthreshold swing of 110 mV dec −1 at V DS = 0.5 V and a small drain induced barrier lowering of 50 mV V −1 .